Youth Participation in Management of Deli Watershed (DAS Deli) in Medan - Hutasuhut, Ikhwan Kurnia; Sihombing, Marlon; Maas, Linda Trimurni (Journal of Environmental and Development Studies, 2022)
The current condition of the Deli Watershed (Daerah Aliran Sungai/DAS Deli) is in an appalling condition. This is indicated by several indicators experienced by the Deli Watershed, such as the decreasing amount of forests, polluted river water, slums along the river banks, silting of rivers, garbage dumped into rivers, so that all such conditions result in frequent floods in the City Field. This has become the author's interest to conduct a study entitled "Youth Participation in Management of Deli Watersheds (Daerah Aliran Sungai/DAS Deli) in Medan". This research use desciptive qualitative approach. The results showed that youth participation was still lacking in the planning/process of preparing and evaluating watershed management. While in terms of implementation, utilization and monitoring of youth, it is enough to participate. As for the obstacles faced by youth in their participation such as lack of human resources, lack of tools and technology, low government response, and lack of public awareness. This study also formulated strategies for increasing youth participation through the SWOT (Streingths, Weaknesses, Opportunities, Threats) analysis approach and calculation of internal factor evaluation (IFE) and evaluation of external factors (EEF) with. Based on the calculation results, the SO strategy gets the highest score with a total score of 3.56.